1998
DOI: 10.1073/pnas.95.16.9208
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte nuclear factor-1 acts as an accessory factor to enhance the inhibitory action of insulin on mouse glucose-6-phosphatase gene transcription

Abstract: Glucose-6-phosphatase catalyzes the terminal step in the gluconeogenic and glycogenolytic pathways. Transcription of the gene encoding the glucose-6-phosphatase catalytic subunit (G6Pase) is stimulated by cAMP and glucocorticoids whereas insulin strongly inhibits both this induction and basal G6Pase gene transcription. Previously, we have demonstrated that the maximum repression of basal G6Pase gene transcription by insulin requires two distinct promoter regions, designated A (from ؊271 to ؊199) and B (from ؊1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
70
4
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(78 citation statements)
references
References 58 publications
3
70
4
1
Order By: Relevance
“…This confirms previous reports demonstrating that the IRU of the Glc-6-Pase promoter is able to transfer insulin regulation to a heterologous promoter (5,26). In addition, we found that the overexpression of the constitutively active PKB was able to suppress the basal expression of the construct pGL(PDH-IRU) but not that of the construct pGL(PDH) (Fig.…”
Section: Fig 4 Binding Of Fkhr To the Iru Transactivates The Promotsupporting
confidence: 80%
See 4 more Smart Citations
“…This confirms previous reports demonstrating that the IRU of the Glc-6-Pase promoter is able to transfer insulin regulation to a heterologous promoter (5,26). In addition, we found that the overexpression of the constitutively active PKB was able to suppress the basal expression of the construct pGL(PDH-IRU) but not that of the construct pGL(PDH) (Fig.…”
Section: Fig 4 Binding Of Fkhr To the Iru Transactivates The Promotsupporting
confidence: 80%
“…Therefore, it might be that the transactivation by FKHR is enhanced by additional proteins, which bind to cis-active elements located in the Glc-6-Pase promoter, but not in the pGL(PDH-IRU) construct. Previous studies suggest that HNF-1 acts as an accessory factor for the insulin effect mediated by the IRU of the Glc-6-Pase promoter (26). A recent report (33) indicates that HNF-1 and the Forkhead protein HNF-3␤ exhibit a synergistic effect on the GLUT2 gene promoter activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations